2014
DOI: 10.1080/15459624.2014.916809
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Safe Handling Guidelines by Health Care Workers Who Administer Antineoplastic Drugs

Abstract: The toxicity of antineoplastic drugs is well documented. Many are known or suspected human carcinogens where no safe exposure level exists. Authoritative guidelines developed by professional practice organizations and federal agencies for the safe handling of these hazardous drugs have been available for nearly three decades. As a means of evaluating the extent of use of primary prevention practices such as engineering, administrative and work practice controls, personal protective equipment (PPE), and barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 19 publications
6
100
0
9
Order By: Relevance
“…This result is in accordance with Boiano, Steege and Sweeney, (2014) [24] who stated that recommended practices are not always followed, despite the availability of safety guidelines developed by professional practice organizations in their study that titled "adherence to safe handling guidelines by health care workers who administer antineoplastic drugs". In addition, VerStrate, (2015) [25] reported that although the toxicity of chemotherapeutic agents is well documented, the nurses that participated in the survey reported a low overall use of safety precautions when administering chemotherapy in his study that titled "exploration of chemotherapy safe-handling practices and identification of knowledge deficits among oncology nurses in the ambulatory care setting".…”
Section: P-value T-testsupporting
confidence: 87%
“…This result is in accordance with Boiano, Steege and Sweeney, (2014) [24] who stated that recommended practices are not always followed, despite the availability of safety guidelines developed by professional practice organizations in their study that titled "adherence to safe handling guidelines by health care workers who administer antineoplastic drugs". In addition, VerStrate, (2015) [25] reported that although the toxicity of chemotherapeutic agents is well documented, the nurses that participated in the survey reported a low overall use of safety precautions when administering chemotherapy in his study that titled "exploration of chemotherapy safe-handling practices and identification of knowledge deficits among oncology nurses in the ambulatory care setting".…”
Section: P-value T-testsupporting
confidence: 87%
“…Because of recommended practices are not always followed, training and education for health care workers are required [34,35]. Training is essential both in terms of risk awareness and the appropriate response to exposure [36].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…27 Participants' responses suggested that such equipment was not always used, a finding that is consistent with other studies, which have concluded that health care workers' compliance with gloves and other personal protective equipment is inadequate. 18,30,31 One limitation of this study was that full identification of all contributing causes was not possible from participants' responses. In most cases, participants would not be aware of the less-visible factors that fall under the purview of an organization's management team, including organization-wide policies and procedures that concern training for safe drug handling and hazard notification (i.e., warning of the presence of antineoplastic drugs), which would have been beneficial to prevent some of the exposure incidents.…”
Section: Contributing Causementioning
confidence: 99%